2008
DOI: 10.1021/om800626b
|View full text |Cite
|
Sign up to set email alerts
|

m-Terphenyl Anchored Palladium Diphosphinite PCP-Pincer Complexes That Promote the Suzuki−Miyaura Reaction Under Mild Conditions

Abstract: Diphosphinite PCP-pincer pro-ligands anchored by a meta-terphenyl backbone were synthesized. These pro-ligands, [2,6-(2-Ph2POC6H4)2C6H3X] (3a X = I, 3b X = Br) and [2,6-(2- i Pr2POC6H4)2C6H3X] (4a X = I, 4b X = Br) upon reaction with Pd2(dba)3 yield PCP palladium pincer complexes [2,6-(2-Ph2POC6H4)2C6H3PdX] (5a X = I, 5b X = Br) and [2,6-(2- i Pr2POC6H4)2C6H3PdX] (6a X = I, 6b X = Br). The structures of 5a−b and 6a−b were determined by single crystal X-ray diffraction analyses. Complexes 5b and 6b were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Compound 2 had proved versatile in the formation of N-C-N and P-C-P pincer ligand precursors [6][7][8][9], and as expected, did so for an S-C-S analogue. Thus reaction of 2 and Li[S(p-Tol)] (freshly prepared by reaction of the thiol with nBuLi) readily yields compound 3 as a yellow oil in 87% yield (Scheme 3) [14].…”
Section: Synthesis Of Pincer Ligand Precursor and Pincer Complexsupporting
confidence: 69%
See 1 more Smart Citation
“…Compound 2 had proved versatile in the formation of N-C-N and P-C-P pincer ligand precursors [6][7][8][9], and as expected, did so for an S-C-S analogue. Thus reaction of 2 and Li[S(p-Tol)] (freshly prepared by reaction of the thiol with nBuLi) readily yields compound 3 as a yellow oil in 87% yield (Scheme 3) [14].…”
Section: Synthesis Of Pincer Ligand Precursor and Pincer Complexsupporting
confidence: 69%
“…Another attribute displayed is the great adaptability and variability of the ligand platform. Our recent efforts [6][7][8][9] have centered on a particular extension of one common pincer ligand motif, the meta-xylyl backbone (A, Chart 1). The introduction of additional aryl rings between the anchoring phenyl ring and the donor atoms forces the resulting pincer complexes (B, Chart 1) to be considerably non-planar owing to larger chelate ring sizes.…”
Section: Introductionmentioning
confidence: 99%
“…13 C { 1 H} NMR (CD 2 Cl 2 /MeOH): δ 21.8 ( 1 J(P2C) = 93.6, 2+3 J(P1C) = 5.0, C1), 40.9 ( 1 J(P1C) = 19.4, 1 J(P2C) = 71.1, 3 J(P3C) = 5.0, C2), 129.9 ( 1 J(P1C) = 47.3, 3 J(P2C) = 5.5, Ph1-C ipso ), 133.6 ( 2 J(P1C) = 14.6, Ph1-C ortho ), 129.2 ( 3 J(P1C) = 12.5, Ph1-C meta ), 132.9 (Ph1-C para ), 126.9 ( 1 J(P2C) = 85.0, 3 J (P1C) = 7.5, Ph2-C ipso ), 132.6 ( 2 J(P2C) = 10.4, Ph2-C ortho ), 129.1 ( 3 J(P2C) = 11.5, Ph2-C meta ), 131.7 (Ph2-C para ). 1 H NMR (CD 2 Cl 2 ): δ 3.95 ( 2 J(P1H) = 9.5, 2 J(P2H) = 7.1, CH 2 ), 7.10-7.80 (m,.…”
Section: General Informationmentioning
confidence: 99%
“…While the reaction of more reactive 4-bromoacetophenone with PhB(OH) 2 in the presence of 0.1 mol% of Uozumi's PCP-bis(phosphinite) pincer Pd complex at 110°C only gave a 60% yield after 24 h [23]. Very recently, Protasiewicz reported that similar m-terphenyl anchored symmetrical PCP-bis(phosphinite) pincer Pd complexes could promote the CC coupling of aryl bromides with p-tolylboronic acid at 50°C and the catalysis was thought to occur via a Pd(0)-Pd(II) catalytic cycle [40]. However, the coupled products were obtained in only moderate yields with 1 mol% of catalyst after 20 h in the case of bromobenzene and 2-bromotoluene (76% and 45%, respectively).…”
Section: B(oh) 2 Armentioning
confidence: 99%